Model of Service-Oriented B2B Integration in the Traffic Safety Area - Slađana Janković; Snežana Mladenović; Krsto Lipovac; Dušan Mladenović; Slavko Vesković (Promet - Traffic&Transportation, 1970)
One class of methods for black spots identification is based on the analysis of: traffic accidents (TA), road parameters, and traffic intensity. The data used in the analysis can be grouped into the information about: roads, persons participating in TA, vehicles participating in TA, traffic accidents and their consequences, and traffic. These categories of data are usually under the jurisdiction of different traffic and non-traffic subjects. Therefore, it is necessary to exchange traffic safety data among the following sources: traffic police, road manager, and health and judicial sector. This paper proposes a model for the exchange and integration of traffic safety data into a single database, which allows the calculation of risks for road sections, as well as the classification and ranking of the sections. The model is based on B2B integration of service-oriented applications. This paper describes a practical example that demonstrates the proposed integration model.